Assessment of Severity in Chronic Thromboembolic Pulmonary Hypertension by Quantitative Parameters of Dual-Energy Computed Tomography. Issue 4 (July 2020) - Tsutsumi, Yoshinori; Iwano, Shingo; Okumura, Naoki; Adachi, Shiro; Abe, Shinji; Kondo, Takahisa; Kato, Katsuhiko; Naganawa, Shinji
Abstract : Objective: The objective of this study was to assess the correlation between dual-energy computed tomography quantitative parameters and hemodynamics in patients with chronic thromboembolic pulmonary hypertension. Methods: Dual-energy computed tomography of 52 chronic thromboembolic pulmonary hypertension patients were evaluated retrospectively. The mean lung perfused blood volume (lung PBV) and the mean pulmonary artery (PA) enhancement measured at pulmonary parenchymal phase were compared with the hemodynamics by Spearman rank correlation coefficient ( r s ) and receiver operating characteristic analysis. Results: Lung PBV was correlated with mean pulmonary arterial pressure ( r s = 0.47, P < 0.001). Pulmonary artery enhancement was correlated with cardiac index ( r s = −0.49, P < 0.001) and pulmonary vascular resistance ( r s = 0.48, P < 0.001). The areas under the curves were 0.86 for lung PBV to predict mean pulmonary arterial pressure of >50 mm Hg and 0.86 for PA enhancement to predict pulmonary vascular resistance of >1000 dyne·s/cm 5 . Conclusions: Lung PBV and PA enhancement could be indicators of hemodynamics.